Description of a new species of the genus Polycaena Staudinger, 1886 (Lepidoptera, Riodinidae) from China with designation of lectotype of Polycaena lua Grum-Grshimailo, 1891 - Krupitsky, Anatoly V.; Shapoval, Nazar A.; Shapoval, Galina N. (Zootaxa, 2024)
A new species, Polycaena eckweileri sp. n., is described from Gansu Province, China. Based on the analysis of the barcode region of the mitochondrial COI gene, the new species belongs to the P. lama Leech, 1893 species group. The new species differs from all the known species of the genus in peculiar characters of the male genitalia. Polycaena eckweileri sp. n. is known to date only from the type locality in Têwo County. The phylogenetic reconstruction of the main lineages of the genus Polycaena based on analysis of a 658 bp region of the COI mitochondrial gene is provided for the first time. Lectotype of Polycaena lua Grum-Grshimailo, 1891 is designated from a series of syntypes deposited in the collection of the Zoological Institute, Russian Academy of Science, St. Petersburg, Russia.